Optimal design of a high-efficiency bidirectional isolated DC-DC converter across a wide range of power transfer - Tan N.M.L.; Abe T.; Akagi H. (2023)
This paper discusses an optimal operating frequency range and optimal switching dead times for a 6-kW, full-bridge, bidirectional isolated dc-dc converter with focus on improving converter efficiency. The optimal frequency of the dc-dc converter is defined by making its frequency-dependent loss equal to its frequency-independent loss. The maximum efficiency of the dc-dc converter operating at 4 kHz is measured at 98.1% during battery charging and at 98.2% during battery discharging. The converter maintains a high efficiency of more than 97% in a wide range of power transfer. 2012 IEEE.